Iturin A Potentiates Differentiation of Intestinal Epithelial Defense Cells by Modulating Keap1/Nrf2 Signaling to Mitigate Oxidative Damage Induced by Heat-Stable Enterotoxin B - Geng-Xiu Zan; Hao-Zhan Qu; Xin-Yang Li; Qi-Liang Peng; Xiao-Fan Wang; Run-Sheng Li; Yu-Guang Zhao; Hui-Chao Yan; Jia-Yi Zhou; Xiu-Qi Wang (Antioxidants)
Intestinal stem cells (ISCs) maintain epithelial renewal through their proliferation and differentiation capabilities, responding to various intestinal insults. However, the impact of iturin A, a natural antimicrobial peptide, on ISC viability and its potential to mitigate heat-stable enterotoxin b (STb)-induced intestinal damage remains unclear. Our recent study demonstrated that oral administration of iturin A enhances tight junction protein expression, accelerates crypt-villus regeneration, and restores epithelial barrier integrity in STb-exposed mice. Furthermore, iturin A promotes ISC proliferation and differentiation, significantly increasing the numbers of goblet and Paneth cells in the jejunum following STb exposure. Notably, iturin A regulates intestinal homeostasis by scavenging reactive oxygen species (ROS), while elevating total antioxidant capacity (T-AOC), superoxide dismutase (SOD), and glutathione peroxidase (GSH-PX) levels in both serum and jejunal mucosa. Mechanistically, iturin A facilitates nuclear factor-erythroid 2- related factor 2 (Nrf2) release by disrupting Kelch-like ECH-associated protein 1 (Keap1), leading to the upregulation of the antioxidant enzyme glutathione peroxidase 4 (GPX4). In conclusion, our findings indicate that iturin A alleviates oxidative stress induced by STb through modulation of the Keap1/Nrf2 pathway and promotes ISC differentiation into goblet and Paneth cells, thereby enhancing resistance to STb-induced damage.